La victimología, perspectiva de la política criminal - Mendizábal Anticona, Walter Jorge (2019)
Victimology has been recognized as an independent science, where the victim is given to be taken as an important part of state policies in different countries, and Peru is not strange to this concern by imposing severe penalties.  The present, makes a review of its legal nature, but, emphasizes the different passivities such as the typology of victimization, revictimization, criminal policy referred to the victim within the state and social system, and regarding feminicide statistics, noting That, it is not the solution to impose tougher penalties.  Likewise, it proposes a form of protection for the victim in order to alleviate the quality of the victim from the economic point of view, which is in Peru, is one of the highest negative consequences and above all a policy of criminological state and, not only criminal dogmatic